COMPARATIVE STUDY OF INDONESIA AND THE NETHERLANDS ON LEGAL PROTECTION FOR SEPARATIST CREDITORS IN BANKRUPTCY WITH THE PRINCIPLE OF CONCURSUS CREDITORUM - Khoiruddin, Amir; Pratama, Dedo Indra; Astriansyah, Denny; Anggriawan, Teddy Prima (Jurnal Meta-Yuridis, 2025)
This study examines the legal protection of secured (separatist) creditors in bankruptcy through a comparative analysis of Indonesian and Dutch legal systems, focusing on the concursus creditorum principle. Secured creditors have preferential rights due to their security interests over debtor assets. Although both countries follow civil law traditions, Indonesia’s implementation under Law No. 37 of 2004 is weakened by limited judicial oversight and the dominant role of curators. In contrast, Dutch law, through the Faillissementswet, allows courts greater authority in supervising secured asset execution, ensuring better balance among creditors.Using a normative juridical method with statutory, comparative, and conceptual approaches, the research finds that the Dutch system offers stronger collective protection and legal fairness. The study concludes that Indonesia needs legal reforms to adopt collective justice principles and improve the proportional legal protection of secured creditors in bankruptcy processes.